2016
DOI: 10.1002/esp.3959
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the transitional behaviour of kaolinite and bentonite suspension flows

Abstract: Past research has demonstrated the dramatic effects that variations in suspended clay can have on the properties of flow by producing a range of transitional flows between turbulent and laminar states, depending on clay concentration and fluid shear. Past studies have been restricted to kaolinite flows, a clay mineral that has relatively weak cohesive properties. This paper extends these studies to suspension flows of bentonite, a clay mineral that attains higher viscosities at far lower volumetric concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…18E) invoked as key supporting evidence (Pickering & Hiscott, 1985;Haughton, 1994Haughton, , 2000Kneller & McCaffrey, 1999;McCaffrey & Kneller, 2001;Grecula et al, 2003;Salles et al, 2014;Patacci et al, 2015;Marini et al, 2016;Tinterri et al, 2016). However, this concept may require some caution, because flow reversals can occur without containment, while thick mud caps may reflect either en masse deposition from a trailing flow of fluidal mud or hemipelagic fallout between consecutive turbidity currents Baas et al, 2009Baas et al, , 2016Leszczy nski et al, 2015). As shown by Ge et al (2017) and the present study, a reverse underflow can be generated on a counter-slope of a few degrees under the load of a decelerated and critically thickened parental current.…”
Section: Sedimentological Implicationssupporting
confidence: 74%
“…18E) invoked as key supporting evidence (Pickering & Hiscott, 1985;Haughton, 1994Haughton, , 2000Kneller & McCaffrey, 1999;McCaffrey & Kneller, 2001;Grecula et al, 2003;Salles et al, 2014;Patacci et al, 2015;Marini et al, 2016;Tinterri et al, 2016). However, this concept may require some caution, because flow reversals can occur without containment, while thick mud caps may reflect either en masse deposition from a trailing flow of fluidal mud or hemipelagic fallout between consecutive turbidity currents Baas et al, 2009Baas et al, , 2016Leszczy nski et al, 2015). As shown by Ge et al (2017) and the present study, a reverse underflow can be generated on a counter-slope of a few degrees under the load of a decelerated and critically thickened parental current.…”
Section: Sedimentological Implicationssupporting
confidence: 74%
“…There are some rare recent studies such as Baas et al . () who compared the behaviour of bentonite to kaolinite in a new set of experiments on suspended flows. This type of investigation should be multiplied and expanded to improve current understanding of the behaviour of clay‐rich turbidity currents in real settings.…”
Section: Discussionmentioning
confidence: 99%
“…Interaction between water chemistry and clay type has not been investigated in detail for fast-moving turbidity currents where turbulence and sedimentwater mixing are suspected to have a great impact. There are some rare recent studies such as Baas et al (2016) who compared the behaviour of bentonite to kaolinite in a new set of experiments on suspended flows. This type of investigation should be multiplied and expanded to improve current understanding of the behaviour of clay-rich turbidity currents in real settings.…”
Section: Do the Deposits From Lake Hazar Validate Flume Experiments Fmentioning
confidence: 99%
“…Recent years have witnessed a step‐change in our understanding of flows that are transitional in their behaviour between turbulent and laminar states, due to the addition of mud in suspension (Wang & Plate, ; Baas & Best, , , ; Baas et al., , , ,b). As an increasing quantity of clay is added to a flow, the particles begin to form flocs and longer chains because of electrostatic bonding, and eventually gel, which may significantly influence the rheology of the flow.…”
Section: The Fluid Dynamics Of Mud‐poor To Mud‐rich Flowsmentioning
confidence: 99%
“…Despite this complexity, experimental studies (Baas & Best, ; Baas et al., , ,b) have shown that, as clays are added to a flow through direct substrate entrainment or abrasion of muddy clasts, a series of predictable and consistent changes occur that modify the mean velocity profile and turbulence structure of the flow (Fig. ).…”
Section: The Fluid Dynamics Of Mud‐poor To Mud‐rich Flowsmentioning
confidence: 99%